Arthrogryposis Multiplex Congenita: Case Report - Aktulay, Ayla; Sağnıç, Saliha; Moraloğlu Tekin, Özlem; Engin Üstün, Yaprak; Yapar Eyi, Elif Gül; Mollamahmutoğlu, Leyla (Gynecology Obstetrics & Reproductive Medicine, 2013)
Arthrogryposis multiplex congenita (AMC), characterized by multiple congenital joint contractures due to decreased fetal movements, is a non-progressive rare syndrome. Prevalence is determined to be 1 in 3000 deliveries. Although it is autosomal recessively inherited, sporadic cases have also been reported. Prenatal diagnosis of AMC is difficult. Here we report a case with a diagnosis of AMC not diagnosed during antenatal follow-up.